Ramp rate modeling for ERCOT look ahead SCED - Xu, X.; Howard, Roy (2013)
Required by NPRR 351, starting June 28, 2012, ERCOT begins to post indicative real time market prices for future intervals. The indicative real time LMP's are calculated by a separated market application, which optimizes over the next hour based on forecasted load demand and wind generation. To explicitly model ramp rate constraints, the optimization model becomes a Mixed Integer Quadratic Programming (MIQP) problem, which imposes a major performance challenge. This paper discusses the measures have been taken during implementation to meet the real time performance requirement. © 2013 IEEE.